The Effect of Communication with Those Charged with‎Governance on ESG Performance, Focusing on Female Directors on The Board - Kim, Suyon (International Journal of Accounting and Economics Studies, 2025)
This study examines the relationship between communication with those charged with ‎governance and ESG performance. Communication with those charged with governance, ‎which refers to formal interactions between external auditors and governance structures, has ‎become increasingly significant in recent years due to heightened regulatory expectations. ‎This trend is driven by regulatory efforts to strengthen disclosure requirements, aiming to ‎enhance accounting transparency. Using data from Korean firms (2019-2020), the empirical ‎results show that more frequent communication with those charged with governance improves ‎ESG performance. Such interactions promote internal governance effectiveness, which in ‎turn supports long-term sustainability. In addition, the presence of female board directors ‎strengthens the positive relationship between governance communication and ESG outcomes, ‎emphasizing the value of board diversity‎.